Concomitant Administration of High-dose Methotrexate and Low-dose Aspirin Without Any Delay in Methotrexate Clearance in a Patient With Osteosarcoma: A Case Report and Review of the Literature. Issue 6 (August 2018) - Renzi, Samuele; Tsimerman, Ekaterina; Taylor, Tracey; Hopyan, Sevan; Koo, Alicia; Gupta, Abha
Abstract : Background: Methotrexate (MTX) is a commonly used agent in the treatment of oncology patients whose clearance depends on renal health maintaining glomerular filtration and tubular secretion. Thus concomitant use of other drugs that utilize the same mechanism of clearance are generally avoided as this may contribute to increased MTX-associated toxicity. Observation: Herein, we describe the use of low-dose aspirin with high-dose MTX in a patient with osteosarcoma. Conclusion: Concomitant aspirin use did not affect the clearance of high-dose MTX and the patient did not experience any MTX-related toxicity including mucositis or renal impairment.